Factors Associated with Hyperemesis Gravidarum at the University of Eastern Indonesia Tourism General Hospital - Yurniati, Yurniati (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Hyperemesis gravidarum (HG) is a condition of excessive nausea and vomiting often experienced during pregnancy. Although common, the impact of HG on the pregnant mother and fetus can be significant. Therefore, this study aims to explore the factors associated with the incidence of HG at the University of Eastern Indonesia Tourism General Hospital. This study aims to Identify factors associated with the incidence of Hyperemesis Gravidarum. Analyze the severity of HG and its impact on the health of pregnant women. Assess the effectiveness of various methods of management and intervention against HG. The research method used was observational research with a case-control study approach. Data were collected through interviews with pregnant women who experienced HG and pregnant women without complaints of excessive nausea. In addition, medical data and medical records were also analyzed to obtain further information. Based on data analysis, it was found that several factors such as family history, maternal age, and nutritional status could be associated with the incidence of Hyperemesis Gravidarum. The severity of HG is also associated with pregnancy complications and fetal growth. Interventions such as nutritional management and psychological support were found to be effective in reducing the severity of HG. Based on the findings of this study, it can be concluded that certain factors have a correlation with the incidence of Hyperemesis Gravidarum. By understanding these factors, better prevention and intervention efforts can be developed to improve maternal and fetal health.